Gas barrier film

JP2025031869AActive Publication Date: 2025-03-07TOPPAN HOLDINGS INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024226978
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-07
Estimated Expiration
2040-06-11

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、熱水処理に対する耐性が高く、環境負荷も抑制されたガスバリア性フィルムを提供できる。さらに酸素バリア性を付与するための皮膜の厚みが薄くても、本来の酸素バリア性を充分に発現でき、酸素バリア性に優れる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031869000001_ABST
    Figure 2025031869000001_ABST
Patent Text Reader

Abstract

To provide a gas barrier film high in resistance to hot water treatment and having a suppressed environmental load.SOLUTION: A gas barrier film 100 includes a substrate 10 mainly composed of polypropylene and an oxygen barrier film 15 formed on a side of a first surface 10a of the substrate. In the infrared spectroscopic measurement of the first surface, a ratio of peak intensity I1 present at 1360 to 1390 cm-1 to peak intensity I2 present at 1440 to 1480 cm-1 satisfies a formula (1): I1 / I2≤1.55. On the first surface, microparticles made of materials other than polypropylene protrude, with the number of microparticles being no more than 100 in a region of 257 μm×259 μm (area 0.067 mm2), and average protrusion height of the microparticles is 2.5 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a gas barrier film. [Background technology]

[0002] Packaging materials used for packaging food, medicine, etc. are required to have the property of preventing the intrusion of gases (water vapor, oxygen, etc.) that denature the contents, in order to prevent deterioration or spoilage of the contents and to maintain their function and quality. For this reason, film materials with gas barrier properties (gas barrier films) are used for these packaging materials.

[0003] As a gas barrier film, one in which a gas barrier layer made of a material having gas barrier properties is provided on the surface of a resin substrate is known. As the gas barrier layer, a metal foil, a metal deposition film, and a film formed by a wet coating method are known. As the film, a resin film formed from a coating agent containing a resin such as a water-soluble polymer or polyvinylidene chloride, and an inorganic layered mineral composite resin film formed from a coating agent containing a water-soluble polymer and an inorganic layered mineral are known to exhibit oxygen barrier properties (for example, see Patent Document 1).

[0004] Further proposed gas barrier layers include a vapor-deposited thin film layer made of an inorganic oxide (see, for example, Patent Document 2), a gas barrier layer in which a gas barrier composite coating containing an aqueous polymer, an inorganic layered compound, and a metal alkoxide is laminated in that order (see, for example, Patent Document 3), and a gas barrier layer containing a polyvalent metal salt of a carboxylic acid, which is a reaction product between a carboxy group of a polycarboxylic acid polymer and a polyvalent metal compound (see, for example, Patent Document 4).

[0005] These gas barrier films have transparency and oxygen blocking properties. As the base film, those made of polyethylene terephthalate (PET) are often used. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6176239 [Patent Document 2] Japanese Unexamined Patent Publication No. 60-49934 [Patent Document 3] JP 2000-254994 A [Patent Document 4] Patent No. 4373797 Summary of the Invention [Problem to be solved by the invention]

[0007] However, gas barrier films in which a coating is provided on the surface of a resin substrate by a wet coating method, a vapor deposition method, or a sputtering method sometimes have unstable oxygen barrier properties depending on the production lot. Specifically, the oxygen barrier properties of the gas barrier films are sometimes inferior to the inherent oxygen barrier properties, that is, the oxygen barrier properties expected from the material constituting the coating and the thickness of the coating. In particular, such problems tend to occur when the thickness of the coating is thin.

[0008] In recent years, there has been an increasing demand for gas barrier films using base films made of polypropylene (PP) or polyethylene (PE) in order to reduce the burden on the environment. However, the inventors' research has revealed that gas barrier films in which a barrier layer is simply formed on a PP base film do not actually have sufficient resistance to hot water treatments such as boiling and retorting.

[0009] In light of the above circumstances, the present invention aims to provide a gas barrier film that can fully exhibit its inherent oxygen barrier properties even when the thickness of a coating for imparting oxygen barrier properties is thin, that has high resistance to hot water treatment, and that also reduces the environmental impact. [Means for solving the problem]

[0010] The present invention relates to a gas barrier film comprising a substrate containing polypropylene as a main component and an oxygen barrier coating on a first surface of the substrate, the gas barrier film having an oxygen barrier property of 1360 to 1390 cm in infrared spectroscopy measurement of the first surface. -1 The peak intensity I1 present at 1440-1480cm -1 When the ratio of the peak intensity I1 present at the peak intensity I2 present at the peak intensity I3 present at the peak intensity I4 present at the peak intensity I5 present at the peak intensity I6 present at the peak intensity I7 present at the peak intensity I8 present at the peak intensity I9 present at the peak intensity I10 at the peak intensity I21 satisfies the following formula (1), a gas barrier film having sufficient hot water resistance with an adhesion strength of 1.0 N / 15 mm or more after hot water treatment and also having reduced environmental impact can be provided. I1 / I2≦1.65 …(1)

[0011] Furthermore, if the number of microparticles added to prevent blocking of the resin substrate is 100 or less per area of ​​250 μm on a side and the average protrusion height is 2.5 μm or less, defects in the oxygen barrier coating that serve as paths for gas permeation are minimized, making it possible to provide a gas barrier film with high oxygen barrier properties.

[0012] The present invention is based on the above findings and has the following aspects. [1] A base material mainly composed of polypropylene, The substrate has an oxygen barrier coating (excluding those containing an inorganic layered compound) on a first surface side thereof, a base layer, or both a base layer and an inorganic oxide layer, between the resin substrate and the oxygen barrier coating; In the infrared spectroscopy of the first surface, -1 The peak intensity I1 present at 1440-1480cm -1 The ratio of the peak intensity I2 present in satisfies the following formula (1), I1 / I2≦1.55 …(1) the first surface has protruding particles formed of a material other than polypropylene; The number of particles is 257 μm × 259 μm (area 0.067 mm 2 ) or less, A gas barrier film, wherein the fine particles have an average protrusion height of 2.5 μm or less. [2] The substrate is The substrate has two or more resin layers including a base layer and a surface layer constituting the first surface, The value of the formula (1) in infrared spectroscopy of the resin layer on the second surface opposite to the first surface is The gas barrier film according to [1], wherein the value of formula (1) is greater than that of the first surface. [3] The gas barrier film according to [1] or [2], wherein the underlayer has a thickness of 0.01 to 1 μm. [4] The underlayer contains an organic polymer as a main component, The gas barrier film according to any one of [1] to [3], wherein the organic polymer comprises at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, or a reaction product of these organic polymers. [5] The gas barrier film according to any one of [1] to [4], wherein the inorganic oxide layer has a thickness of 1 to 200 nm. [6] The gas barrier film according to any one of [1] to [5], wherein the inorganic oxide layer is aluminum oxide or silicon oxide. [7] The gas barrier film according to any one of [1] to [6], wherein the oxygen barrier coating has a thickness of 0.05 to 1 μm. [8] The gas barrier film according to any one of [1] to [7], wherein the oxygen barrier coating is a coating containing at least one of a metal alkoxide, a hydrolysate thereof, or a reaction product thereof, and a water-soluble polymer. [9] The gas barrier film according to [8], wherein the oxygen barrier coating further contains at least one of a silane coupling agent, a hydrolyzate thereof, and a reaction product thereof.

[10] The gas barrier film according to any one of [1] to [7], wherein the oxygen barrier coating contains a polyvalent metal salt of a carboxylic acid which is a reaction product between a carboxy group of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B).

[11] The gas barrier film according to any one of [1] to

[10] , wherein the substrate further comprises a heat-sealable sealant layer, and the sealant layer is bonded to the oxygen barrier coating by an adhesive layer.

[12] After hot water treatment at 120°C for 30 minutes, Oxygen permeability is 5.0cc / m 2 ·day or less, The gas barrier film according to any one of [1] to

[11] , wherein a peel strength between the substrate and the sealant layer is 1.0 N / 15 mm or more. Effect of the Invention

[0013] According to the present invention, a gas barrier film having high resistance to hot water treatment and reduced environmental impact can be provided. Furthermore, even if the thickness of the coating for imparting oxygen barrier properties is thin, the inherent oxygen barrier properties can be sufficiently exhibited, and the film has excellent oxygen barrier properties. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic cross-sectional view of a gas barrier film according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The gas barrier film of the present invention will be described with reference to embodiments.

[0016] Fig. 1 is a schematic cross-sectional view of a gas barrier film 100 according to an embodiment of the present invention. For the sake of convenience, the dimensional ratio in Fig. 1 differs from the actual ratio.

[0017] The gas barrier film 100 comprises a resin substrate 10, an underlayer 13, an inorganic oxide layer 14, and an oxygen barrier coating 15. The inorganic oxide layer 14 may be omitted.

[0018] The substrate 10 has two or more resin layers and includes at least a surface layer 11 and a base layer 12 , and the surface layer 11 includes fine particles 16 .

[0019] The underlayer 13 is positioned in contact with the first surface 10a of the resin substrate 10, and the inorganic oxide layer 14 or the oxygen barrier film 15 is positioned in contact with the opposite surface.

[0020] The gas barrier film 100 has a sealant layer 18 , which is positioned in contact with an adhesive layer 17 , which is positioned in contact with an oxygen barrier coating 15 .

[0021] The substrate 10 has two or more resin layers containing polypropylene as a main component. The substrate of this embodiment has two resin layers: a base layer 12 and a surface layer 11 laminated on the base layer 12.

[0022] The substrate 10 having two or more resin layers can be formed, for example, by coextrusion. The total thickness of the substrate 10, which is the sum of the thicknesses of the base layer 12 and the surface layer 11, can be, for example, 3 to 200 μm, and preferably 15 to 60 μm.

[0023] The resin used as the raw material for each layer of the substrate 10 is mainly polypropylene, from the viewpoints of availability, water vapor barrier properties, and suppression of environmental impact. The polypropylene may be any of homopolymer, random copolymer, block copolymer, and terpolymer. The homopolymer is polypropylene consisting of only propylene alone. The random copolymer is polypropylene in which the main monomer propylene and a different type of comonomer are randomly copolymerized to form a homogeneous phase. The block copolymer is polypropylene in which the main monomer propylene and the above-mentioned comonomer are copolymerized in blocks or polymerized in a rubber-like form to form a heterogeneous phase. The terpolymer is polypropylene in which the main monomer propylene and two types of comonomers different from propylene are copolymerized. These polyolefin resins may be used alone or in a blend of two or more. The raw material for the base layer 12 is preferably any of homopolymer, random copolymer, and block copolymer. The raw material for the surface layer 11 is preferably any of random copolymer, block copolymer, and terpolymer.

[0024] The base layer 12 may contain an additive. The additive can be appropriately selected from various known additives. Examples of the additive include an antiblocking agent (AB agent), a heat stabilizer, a weather stabilizer, an ultraviolet absorber, a lubricant, a slip agent, a nucleating agent, an antistatic agent, an antifogging agent, a pigment, and a dye. Any one of these additives may be used alone, or two or more may be used in combination. Of the above, the lubricant and the slip agent are preferred from the viewpoint of processing suitability. The content of the additive in the base layer 12 can be appropriately adjusted within a range that does not impede the effects of the present invention. The base layer 12 typically does not contain an AB agent.

[0025] The base layer 12 may have a single-layer structure or a multi-layer structure. The thickness of the base layer 12 may be, for example, 3 to 200 μm, or 6 to 30 μm.

[0026] The raw material of the surface layer 11 is preferably any one of a random copolymer, a block copolymer, and a terpolymer.

[0027] The surface layer 11 contains fine particles, typically an AB agent. If the number of fine particles is 100 or less per region of 250 μm on a side and the average protruding height is 5 μm or less, the occurrence of defects that become paths for gas permeation can be suppressed during the formation of the oxygen barrier coating 15, and excellent oxygen barrier properties are exhibited.

[0028] The surface layer 11 may contain additives other than the AB agent. The additives can be appropriately selected from various known additives. Examples of the additives include heat stabilizers, weather stabilizers, UV absorbers, lubricants, slipping agents, nucleating agents, antistatic agents, antifogging agents, pigments, and dyes. Any one of these additives may be used alone, or two or more may be used in combination. Of the above, lubricants and slipping agents are preferred from the viewpoint of processing suitability. The content of the additives in the surface layer 11 can be appropriately adjusted within a range that does not impede the effects of the present invention.

[0029] The thickness of the surface layer 11 may be, for example, 0.1 to 10 μm, or may be 0.5 to 5.0 μm.

[0030] The fine particles 16 are typically AB agents, and are solid particles, and examples thereof include organic particles and inorganic particles. Examples of organic particles include polymethyl methacrylate particles, polystyrene particles, and polyamide particles. These organic particles are obtained, for example, by emulsion polymerization or suspension polymerization. Examples of inorganic particles include silica particles, zeolite, talc, kaolinite, and feldspar. These AB agents may be used alone or in combination of two or more. As the fine particles 16, polymethyl methacrylate particles are preferred for organic systems, and silica particles are preferred for inorganic systems.

[0031] The average particle size of the fine particles 16 is preferably 0.1 μm or more and 5 μm or less, taking into consideration the appearance of the first surface 10a, the transparency of the substrate 10, the possibility of the fine particles 16 falling off, and anti-blocking performance.

[0032] The amount of the fine particles 16 added to the surface layer 11 is, for example, 0.1 to 0.4 mass % with respect to the total mass of the surface layer 11. The amount of the fine particles 16 added to the surface layer 11 is specifically calculated by the following formula. Amount of fine particles added [mass%] = {(i) / 100} × {(ii) / 100} × 100 In the formula, (i) represents the concentration (mass%) of fine particles in masterbatch resin chips obtained by adding fine particles to a resin, stirring the mixture, feeding the mixture into an extruder and kneading the mixture, and then melt-extruding the mixture into pellets; (ii) indicates the concentration (mass %) of masterbatch resin chips containing fine particles relative to the total mass of resin pellets constituting surface layer 11 when masterbatch resin chips containing fine particles are blended with a resin not containing fine particles.

[0033] The fine particles 16 may be contained on the second surface 10b of the substrate 10, and are preferably contained therein in consideration of anti-blocking performance.

[0034] The resin substrate 10 is preferably a coextruded film in which the layers including the surface layer 11 and the base layer 12 are laminated by coextrusion. The resin substrate 10 may be a stretched film or an unstretched film.

[0035] The resin substrate 10 preferably has a biaxially oriented polypropylene film. Since biaxially oriented polypropylene films have particularly excellent water vapor barrier properties, the gas barrier film 100 has excellent water vapor barrier properties by having a biaxially oriented polypropylene film. The biaxially oriented polypropylene film may be at least one of homopolymers, random copolymers, block copolymers, etc., processed into a film shape. The biaxially oriented polypropylene film is preferably a coextruded film.

[0036] The thickness of the resin substrate 10 can be adjusted depending on the application, the desired properties, etc., and is not particularly limited, but may be, for example, 3 to 200 μm, or may be 6 to 30 μm. The thickness of the resin substrate 10 is the thickness of a portion where no protrusions resulting from the fine particles 16 are present.

[0037] The surfaces (first surface 10a, second surface 10b) of the resin substrate 10 may be subjected to at least one treatment selected from the group consisting of chemical treatment, solvent treatment, corona treatment, plasma treatment and ozone treatment.

[0038] (base layer) The underlayer 13 is provided between the resin substrate 10 and the inorganic oxide layer 14 or the oxygen barrier film 15 .

[0039] The underlayer 13 is a layer containing an organic polymer as a main component, and is sometimes called a primer layer. By providing the underlayer 13, it is possible to improve the film-forming property and adhesion strength of the inorganic oxide layer 14 or the oxygen barrier film 15.

[0040] The content of the organic polymer in the underlayer 13 may be, for example, 70% by mass or more, or 80% by mass or more. Examples of the organic polymer include polyacrylic resin, polyester resin, polycarbonate resin, polyurethane resin, polyamide resin, polyolefin resin, polyimide resin, melamine resin, and phenol resin. Considering the hot water resistance of the adhesive strength between the resin substrate 10 and the inorganic oxide layer 14 or the oxygen barrier film 15, it is preferable that the underlayer 13 contains at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, or a reaction product of these organic polymers. The underlayer 13 may also contain a silane coupling agent, an organic titanate, or a modified silicone oil.

[0041] More preferred examples of the organic polymer include an organic polymer having a urethane bond produced by the reaction of a polyol having two or more hydroxyl groups at the polymer terminal with an isocyanate compound, and / or an organic polymer containing a reaction product of a polyol having two or more hydroxyl groups at the polymer terminal with an organic silane compound such as a silane coupling agent or a hydrolyzate thereof.

[0042] Examples of polyols include at least one selected from acrylic polyol, polyvinyl acetal, polystyrene polyol, and polyurethane polyol. The acrylic polyol may be obtained by polymerizing an acrylic acid derivative monomer, or may be obtained by copolymerizing an acrylic acid derivative monomer with another monomer. Examples of the acrylic acid derivative monomer include ethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate. Examples of the monomer to be copolymerized with the acrylic acid derivative monomer include styrene.

[0043] The isocyanate compound has the effect of increasing the adhesion between the resin substrate 10 and the inorganic oxide layer 14 or the oxygen barrier film 15 by forming a urethane bond by reacting with the polyol. That is, the isocyanate compound functions as a crosslinking agent or a curing agent. Examples of the isocyanate compound include aromatic tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), aliphatic xylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI), and isophorone diisocyanate (IPDI) monomers, polymers thereof, and derivatives thereof. The above-mentioned isocyanate compounds may be used alone or in combination of two or more.

[0044] Examples of silane coupling agents include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane. The organic silane compound may be a hydrolyzate of these silane coupling agents. The organic silane compound may contain one of the above-mentioned silane coupling agents and their hydrolyzates alone, or two or more of them in combination.

[0045] The underlayer 13 can be formed by preparing a mixed solution by mixing the above-mentioned components in an organic solvent in any ratio, and using the mixed solution prepared on the first surface 10a of the resin substrate 10. The mixed solution may contain, for example, a curing accelerator such as a tertiary amine, an imidazole derivative, a metal salt compound of a carboxylic acid, a quaternary ammonium salt, or a quaternary phosphonium salt; an antioxidant such as a phenol-based, sulfur-based, or phosphite-based antioxidant; a leveling agent; a flow control agent; a catalyst; a crosslinking reaction accelerator; a filler, etc.

[0046] The mixed liquid can be coated on the resin substrate 10 by using a known printing method such as offset printing, gravure printing, or silk screen printing, or a known application method such as roll coating, knife edge coating, or gravure coating. After coating, the mixture can be heated to, for example, 50 to 200° C., and dried and / or cured to form the undercoat layer 13.

[0047] The thickness of the underlayer 13 is not particularly limited and may be, for example, 0.005 to 5 μm. The thickness may be adjusted depending on the application or the desired characteristics. The thickness of the underlayer 13 is preferably 0.01 to 1 μm, more preferably 0.01 to 0.5 μm. If the thickness of the underlayer 13 is 0.01 μm or more, sufficient adhesive strength between the resin substrate 10 and the inorganic oxide layer 14 or the oxygen barrier film 15 is obtained, and the oxygen barrier property is also good. If the thickness of the underlayer 27 is 1 μm or less, it is easy to form a uniform coating surface, and the drying load and manufacturing costs can be suppressed.

[0048] (Inorganic oxide layer) Examples of materials for the inorganic oxide layer 14 include aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, tin oxide, zinc oxide, and indium oxide. In particular, aluminum oxide or silicon oxide is preferred because it has excellent productivity and excellent oxygen barrier properties and water vapor barrier properties in heat resistance and wet heat resistance. The inorganic oxide layer 14 may contain one of these materials alone or two or more of them in combination. The thickness of the inorganic oxide layer 14 is preferably 1 to 200 nm. If the thickness is 1 nm or more, excellent oxygen barrier properties and water vapor barrier properties are obtained, and if the thickness is 200 nm or less, the manufacturing cost can be kept low, cracks due to external forces such as bending and pulling are unlikely to occur, and deterioration of the barrier properties can be suppressed. The inorganic oxide layer 14 can be formed by a known film formation method such as a vacuum deposition method, a sputtering method, an ion plating method, or a plasma vapor phase growth method (CVD).

[0049] (Oxygen barrier film) The oxygen barrier film 15 may be a known oxygen barrier film formed by a wet coating method. The oxygen barrier film 15 is obtained by forming a coating film made of a coating agent on the underlayer 13 or the inorganic oxide layer 14 by a wet coating method, and drying the coating film. The coating film is a wet film, and the film is a dry film.

[0050] The oxygen barrier film 15 is preferably a film containing at least one of a metal alkoxide and its hydrolysate or its reaction product, and a water-soluble polymer (organic-inorganic composite film), and more preferably a film further containing at least one of a silane coupling agent and its hydrolysate.

[0051] Examples of metal alkoxides and their hydrolysates contained in the organic-inorganic composite film include those represented by the general formula M(OR), such as tetraethoxysilane [Si(OC2H5)4] and triisopropoxyaluminum [Al(OC3H7)3]. n and hydrolysates thereof. One of these may be contained alone, or two or more of them may be contained in combination.

[0052] The total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane is, for example, 40 to 70 mass%. From the viewpoint of further reducing oxygen permeability, the lower limit of the total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane may be 50 mass%. From the same viewpoint, the upper limit of the total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane may be 65 mass%.

[0053] The water-soluble polymer contained in the organic-inorganic composite film is not particularly limited, and examples thereof include polyvinyl alcohol-based polymers, polysaccharides such as starch, methyl cellulose, and carboxymethyl cellulose, and acrylic polyol-based polymers. From the viewpoint of further improving the oxygen gas barrier property, the water-soluble polymer preferably contains a polyvinyl alcohol-based polymer. The number average molecular weight of the water-soluble polymer is, for example, 40,000 to 180,000.

[0054] A water-soluble polymer such as polyvinyl alcohol can be obtained by, for example, saponifying polyvinyl acetate (including partial saponification). This water-soluble polymer may have several tens of percent of acetate groups remaining, or may have only a few percent of acetate groups remaining.

[0055] The content of the water-soluble polymer in the organic-inorganic composite film is, for example, 15 to 50 mass%. The lower limit of the content of the water-soluble polymer in the organic-inorganic composite film may be 20 mass% from the viewpoint of further reducing oxygen permeability. The upper limit of the content of the water-soluble polymer in the organic-inorganic composite film may be 45 mass% from the viewpoint of further reducing oxygen permeability.

[0056] The silane coupling agent and its hydrolysate contained in the organic-inorganic composite film include silane coupling agents having organic functional groups. Such silane coupling agents and their hydrolysates include ethyltrimethoxysilane, vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and their hydrolysates. One of these may be contained alone, or two or more may be contained in combination.

[0057] At least one of the silane coupling agent and its hydrolysate is preferably one having an epoxy group as an organic functional group. Examples of the silane coupling agent having an epoxy group include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. The silane coupling agent having an epoxy group and its hydrolysate may have an organic functional group other than the epoxy group, such as a vinyl group, an amino group, a methacryl group, or a ureyl group.

[0058] A silane coupling agent having an organic functional group and its hydrolysate can further improve the oxygen barrier property of the oxygen barrier coating 15 and the adhesion to the underlayer 13 or the inorganic oxide layer 14 through the interaction between the organic functional group and the hydroxyl group of the water-soluble polymer. In particular, an oxygen barrier coating 15 that is particularly excellent in oxygen barrier property and adhesion to the underlayer 13 or the inorganic oxide layer 14 can be formed through the interaction between the epoxy group of the silane coupling agent or its hydrolysate and the hydroxyl group of polyvinyl alcohol.

[0059] The total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film is, for example, 1 to 15 mass%. From the viewpoint of further reducing oxygen permeability, the lower limit of the total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film may be 2 mass%. From the same viewpoint, the upper limit of the total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film may be 12 mass%.

[0060] The organic-inorganic composite film may contain a crystalline inorganic layered compound having a layered structure. Examples of the inorganic layered compound include clay minerals such as kaolinite, smectite, and mica. These may be used alone or in combination of two or more. The particle size of the inorganic layered compound is, for example, 0.1 to 10 μm. The aspect ratio of the inorganic layered compound is, for example, 50 to 5000.

[0061] As the inorganic layered compound, a clay mineral of the smectite group is preferable because a water-soluble polymer can be inserted between the layers of the layered structure (intercalation) to form a film having excellent oxygen barrier properties and adhesive strength. Specific examples of the clay mineral of the smectite group include montmorillonite, hectorite, saponite, water-swellable synthetic mica, etc.

[0062] Another preferred example of the oxygen barrier film 15 is a film containing a polyvalent metal salt of carboxylic acid, which is a reaction product between a carboxy group of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) (polycarboxylic acid polyvalent metal salt film). In this case, the film may be a polycarboxylic acid polyvalent metal salt film formed by applying a coating agent in which a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) are mixed and then dried by heating, or may be a polycarboxylic acid polyvalent metal salt film formed by applying a coating agent mainly composed of a polycarboxylic acid polymer (A) and drying to form a film A, applying a coating agent mainly composed of a polyvalent metal compound (B) on the film A, and then drying to form a film B, and then allowing a crosslinking reaction between the A / B layers.

[0063] [Polycarboxylic acid polymer (A)] A polycarboxylic acid polymer is a polymer having two or more carboxy groups in a molecule. Examples of polycarboxylic acid polymers include (co)polymers of ethylenically unsaturated carboxylic acids; copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers; and acidic polysaccharides having a carboxyl group in a molecule, such as alginic acid, carboxymethylcellulose, and pectin. Examples of the ethylenically unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of the ethylenically unsaturated monomers copolymerizable with the ethylenically unsaturated carboxylic acids include saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconates, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile. These polycarboxylic acid polymers may be used alone or in combination of two or more.

[0064] Of the above, from the viewpoint of the gas barrier properties of the resulting gas barrier film, preferred components are polymers containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid, and crotonic acid, and particularly preferred are polymers containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid.

[0065] In the polymer, the proportion of the structural units derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is preferably 80 mol% or more, more preferably 90 mol% or more (wherein the total of all structural units constituting the polymer is 100 mol%). The polymer may be a homopolymer or a copolymer. When the polymer is a copolymer containing structural units other than the above structural units, examples of the other structural units include structural units derived from ethylenically unsaturated monomers copolymerizable with the above-mentioned ethylenically unsaturated carboxylic acid.

[0066] The number average molecular weight of the polycarboxylic acid polymer is preferably within the range of 2,000 to 10,000,000, and more preferably 5,000 to 1,000,000. If the number average molecular weight is less than 2,000, the resulting gas barrier film cannot achieve sufficient water resistance, and the gas barrier property and transparency may deteriorate due to moisture, or whitening may occur. On the other hand, if the number average molecular weight exceeds 10,000,000, the viscosity of the coating agent when forming the oxygen barrier film 15 may increase, and the coatability may be impaired. The number average molecular weight is a polystyrene-equivalent number average molecular weight determined by gel permeation chromatography (GPC).

[0067] In the case where a coating agent mainly composed of a polycarboxylic acid polymer (A) is applied and dried to form an A film, and then the B film is formed, a part of the carboxyl groups of the polycarboxylic acid polymer may be neutralized in advance with a basic compound. By neutralizing a part of the carboxyl groups of the polycarboxylic acid polymer in advance, the water resistance and heat resistance of the A film can be further improved. As the basic compound, at least one basic compound selected from the group consisting of polyvalent metal compounds, monovalent metal compounds, and ammonia is preferable. As the polyvalent metal compound, the compounds exemplified in the description of the polyvalent metal compound (B) described later can be used. As the monovalent metal compound, for example, sodium hydroxide, potassium hydroxide, etc. can be mentioned.

[0068] Various additives can be added to the coating agent containing the polycarboxylic acid polymer (A) as the main component. These include crosslinking agents, curing agents, leveling agents, defoamers, antiblocking agents, antistatic agents, dispersants, surfactants, softeners, stabilizers, film-forming agents, thickeners and the like, within the range that does not impair the barrier performance.

[0069] The solvent used in the coating agent containing polycarboxylic acid polymer (A) as the main component is preferably an aqueous medium. Examples of the aqueous medium include water, water-soluble or hydrophilic organic solvents, or mixtures thereof. The aqueous medium usually contains water or water as the main component. The content of water in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more. Examples of the water-soluble or hydrophilic organic solvent include alcohols such as methanol, ethanol, and isopropanol, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran, cellosolves, carbitols, and nitriles such as acetonitriles.

[0070] [Polyvalent metal compounds (B)] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of polycarboxylic acid, and examples thereof include zinc oxide particles, magnesium oxide particles, magnesium methoxide, copper oxide, calcium carbonate, etc. These may be used alone or in combination. Zinc oxide is preferred from the viewpoint of the oxygen barrier properties of the oxygen barrier coating.

[0071] Zinc oxide is an inorganic material capable of absorbing ultraviolet light. The average particle size of the zinc oxide particles is not particularly limited, but from the viewpoints of gas barrier properties, transparency, and coating suitability, the average particle size is preferably 5 μm or less, more preferably 1 μm or less, and particularly preferably 0.1 μm or less.

[0072] When a coating agent mainly composed of a polyvalent metal compound (B) is applied and dried to form a B film, various additives may be contained in addition to zinc oxide particles as necessary within the range that does not impair the effects of the present invention. The additives may include a resin soluble or dispersible in a solvent used in the coating agent, a dispersant soluble or dispersible in the solvent, a surfactant, a softener, a stabilizer, a film-forming agent, a thickener, etc.

[0073] Among the above, it is preferable to contain a resin that is soluble or dispersible in the solvent used in the coating agent. This improves the coatability and film-forming properties of the coating agent. Examples of such resins include alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluorine resins, epoxy resins, and isocyanate resins.

[0074] It is also preferable to contain a dispersant that is soluble or dispersible in the solvent used in the coating agent. This improves the dispersibility of the polyvalent metal compound. As the dispersant, an anionic surfactant or a nonionic surfactant can be used. As the surfactant, various surfactants such as (poly)carboxylate, alkyl sulfate, alkylbenzene sulfonate, alkylnaphthalene sulfonate, alkylsulfosuccinate, alkyldiphenylether disulfonate, alkylphosphate, aromatic phosphate, polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, alkylallyl sulfate, polyoxyethylene alkylphosphate, sorbitan alkyl ester, glycerin fatty acid ester, sorbitan fatty acid ester, sucrose fatty acid ester, polyethylene glycol fatty acid ester, polyoxyethylene sorbitan alkyl ester, polyoxyethylene alkylallyl ether, polyoxyethylene derivative, polyoxyethylene sorbitol fatty acid ester, polyoxy fatty acid ester, and polyoxyethylene alkylamine can be mentioned. These surfactants may be used alone or in combination of two or more.

[0075] When an additive is contained in a coating agent mainly composed of a polyvalent metal compound (B), the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) is preferably within the range of 30:70 to 99:1, and more preferably within the range of 50:50 to 98:2.

[0076] Examples of the solvent used in the coating agent containing polyvalent metal compound (B) as a main component include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of coating property, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. From the viewpoint of manufacturability, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred.

[0077] When a coating agent containing a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) is applied and dried to form a polycarboxylic acid polyvalent metal salt film, the polycarboxylic acid polymer (A) and the polyvalent metal compound (B) are mixed with a resin or dispersant that can be dissolved or dispersed in water or alcohol as a solvent, and additives as necessary, and the mixture is applied and dried by a known coating method to form a polycarboxylic acid polyvalent metal salt film. Examples of the coating method include casting, dipping, roll coating, gravure coating, screen printing, reverse coating, spray coating, kit coating, die coating, metaling bar coating, chamber doctor combined coating, curtain coating, etc.

[0078] The thickness of the oxygen barrier film 15 is set according to the required oxygen barrier property, and may be, for example, 0.05 to 5 μm. The thickness of the oxygen barrier film 15 is preferably 0.05 to 1 μm, more preferably 0.1 to 0.5 μm. If the thickness of the oxygen barrier film 15 is 0.05 μm or more, sufficient oxygen barrier property is easily obtained. If the thickness of the oxygen barrier film 15 is 1 μm or less, the presence or absence of protrusions derived from the AB agent on the first surface 10a has a large effect on the oxygen barrier property, and the usefulness of the present invention is high. In addition, if the thickness of the oxygen barrier film 15 is 1 μm or less, it is easy to form a uniform coating surface, and the drying load and manufacturing costs can be suppressed.

[0079] Gas barrier films having the above-mentioned organic-inorganic composite film or the above-mentioned polyvalent metal salt film of polycarboxylic acid as a gas barrier film exhibit excellent oxygen barrier properties even when subjected to boiling treatment or retort sterilization treatment, and when laminated with a sealant film, have sufficient adhesion strength and seal strength as a packaging material for boiling or retort treatment. Furthermore, they have advantages such as transparency not found in metal foils or metal vapor-deposited films, excellent bending resistance and stretching resistance, and no risk of generating harmful substances such as dioxins.

[0080] The sealant layer 18 is a layer that is bonded by heat fusion when forming a bag-shaped package or the like using the gas barrier film 100. Examples of materials for the sealant layer 18 include resin materials such as polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-methacrylic acid copolymer, ethylene-methacrylic acid ester copolymer, ethylene-acrylic acid copolymer, ethylene-acrylic acid ester copolymer, and metal crosslinked products thereof. The thickness of the sealant layer 60 is determined depending on the purpose, but can be in the range of 15 to 200 μm, for example.

[0081] The adhesive layer 17 bonds the sealant layer 18 and the oxygen barrier film 15. By using the adhesive layer 17, the resin film that becomes the sealant layer 18 and the substrate 10 on which the oxygen barrier film 15 is formed can be bonded together by dry lamination. An example of the material for the adhesive layer 17 is a two-component curing polyurethane adhesive.

[0082] A packaging material can be prepared by laminating a printed layer, an intervening film, a sealant layer, etc., on the oxygen barrier film 15. When laminating, an extrusion lamination method may be used in which a sealant is formed directly on the coating layer 30 without the use of an adhesive.

[0083] The first surface 10a of the substrate 10 has a wavelength of 1370 to 1380 cm in infrared spectroscopy. -1 The peak intensity (I1) at 1450-1460cm -1 The intensity ratio between the peak intensity (I1) and the peak intensity (I2) present at the first surface 10a is within the range of formula (1). That is, I1 is 1.65 times or less than I2. In this embodiment, this intensity ratio is brought about by the material properties of the surface layer 11 constituting the first surface 10a. I1 / I2≦1.65 …(1)

[0084] The value of the above formula (1) indicates the proportion of polypropylene in the resin components at the measurement point. I1 indicates the amount of polypropylene, and I2 indicates the sum of polyethylene and polypropylene. Therefore, the value of formula (1) is larger for homopolymers than for copolymers and terpolymers, and in copolymers and terpolymers, the value of formula (1) decreases as the amount of components other than polypropylene increases.

[0085] The inventors conducted various studies when constructing a gas barrier film using a base material mainly composed of polypropylene. As a result, they found that in the first surface 10a on which the oxygen barrier coating 15 is formed, the adhesion strength of the gas barrier layer is improved when the proportion of polypropylene is low within the range of the main component. The value of formula (1) in the first surface 10a is preferably 1.55 or less, and more preferably 1.50 or less.

[0086] As described above, the gas barrier film 100 of this embodiment is configured so that the gas barrier layer exhibits suitable gas barrier properties, is well bonded to the substrate, and is not easily peeled off, while maintaining a mono-material structure mainly composed of polypropylene to reduce environmental impact.

[0087] As a result of further investigation, the inventors found that the overall properties of the substrate 10 are further improved by adding the base layer 12 having a larger value of formula (1) to the surface layer 11 including the first surface having the above-mentioned properties. By laminating a layer having a larger value of formula (1), i.e., a layer having a higher proportion of polypropylene than the layer including the first surface, the heat resistance of the substrate 10 as a whole is improved. As a result, sufficient heat can be applied to the substrate 10 when forming the oxygen barrier coating 15, and the barrier performance of the oxygen barrier coating 15 can be improved. Furthermore, when the manufactured gas barrier film is subjected to a hot water treatment such as a retort treatment or a boiling treatment, the base layer 12 suppresses the shrinkage of the surface layer 11, and thus the shrinkage causes cracks in the oxygen barrier coating 15, which leads to a decrease in the gas barrier function, and the oxygen barrier coating 15 is easily peeled off from the substrate 10.

[0088] From this viewpoint, the value of the above formula (1) on the second surface 10b formed by the base layer 12 is preferably larger than that on the first surface 10a, and is more preferably 1.65 or more.

[0089] (Method of manufacturing gas barrier film) The gas barrier film 100 can be produced by forming an underlayer 13, or both the underlayer 13 and the inorganic oxide layer 14, on the first surface 10a of the resin substrate 10, and then forming an oxygen barrier coating 15 on the underlayer 13 or the inorganic oxide layer 14.

[0090] The resin substrate 10 may be a commercially available product or may be produced by a known method.

[0091] As described above, the undercoat layer 13 is obtained by forming a coating film made of a coating agent on the first surface 10a of the resin substrate 10 by a wet coating method, and drying the coating film. As the wet coating method, known wet coating methods such as roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating can be used. As a method for drying the coating film made of a coating agent, known drying methods such as hot air drying, hot roll drying, and infrared irradiation can be used. As a drying condition, for example, a condition of 90° C. for 10 seconds can be mentioned.

[0092] The inorganic oxide layer 14 is obtained by forming a film on the underlayer 13 by the above-mentioned vacuum deposition method, sputtering method, ion plating method, plasma chemical vapor deposition (CVD) method, or the like.

[0093] The oxygen barrier film 15 is obtained by forming a coating film made of the above-mentioned coating agent on the underlayer 13 or the inorganic oxide layer 14 by a wet coating method, and drying the coating. As the wet coating method, known wet coating methods such as roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating can be used. As a method for drying the coating film made of the coating agent, known drying methods such as hot air drying, hot roll drying, and infrared irradiation can be used. As a drying condition, for example, a condition of 90°C for 10 seconds can be mentioned. The oxygen barrier film 15 may be formed by one coating and drying, or may be formed by repeating multiple coatings and dryings using the same or different coating agents.

[0094] (Action and effect) The gas barrier film 100 described above includes a resin substrate 10 having at least a surface layer 11 and a base layer 12, and a base layer 13 or a base layer 13 and an inorganic oxide layer 14 on a first surface 10a of the resin substrate 10, and further includes an oxygen barrier coating 15. The number of fine particles 16 contained in the surface layer 11 is 100 or less per area of ​​250 μm on a side, and the average protruding height of the fine particles 16 is 2.5 μm or less, so that the inherent oxygen barrier property can be fully exhibited and the gas barrier film 100 has excellent oxygen barrier properties. In addition, the thickness of the oxygen barrier coating 15 can be reduced, so that the gas barrier film 100 can be provided at low cost.

[0095] The reason why the oxygen barrier film 15 can fully exhibit its inherent oxygen barrier properties even if it is thin is believed to be as follows.

[0096] Generally, resin substrates contain fine particles 16 of an AB agent to prevent blocking, and protrusions due to the AB agent exist on both sides (first and second sides) of the resin substrate. When a coating agent is applied to this resin substrate by a wet coating method, particularly when the amount of coating is small, a coating film is not formed locally at the positions of the protrusions, resulting in defects. These defects become paths for gas permeation, and oxygen barrier properties are not fully expressed.

[0097] Although the present invention has been described above by showing the embodiments, the present invention is not limited to the above-mentioned embodiments. Each configuration and their combination in the above-mentioned embodiments is an example, and addition, omission, substitution, and other modifications of the configuration are possible within the scope of the gist of the present invention.

[0098] The gas barrier film may further have a printing layer, an anchor coat layer, an overcoat layer, a light-shielding layer, an oxygen absorbing layer, an adhesive layer, a heat-sealable heat-fusible layer, and other functional layers, as necessary.

[0099] When the gas barrier film has a heat-sealable sealant layer 18, the sealant layer 18 is disposed on at least one outermost surface of the gas barrier film. The gas barrier film has the sealant layer 18, so that the gas barrier film can be sealed by heat sealing. The sealant layer 18 can be laminated by a known dry lamination method, extrusion lamination method, or the like, using a known adhesive such as a polyurethane-based, polyester-based, or polyether-based adhesive. EXAMPLES

[0100] The present invention will be described in more detail below with reference to examples and comparative examples, although the present invention is not limited to the following examples.

[0101] [Materials used] <Resin substrate> α1: Biaxially oriented polypropylene film (product name: M-1, thickness 20 μm, one-sided corona treatment, manufactured by Mitsui Chemicals Tohcello Co., Ltd.). α2: Biaxially oriented polypropylene film (product name: ME-1, thickness 20 μm, one-sided corona treatment, manufactured by Mitsui Chemicals Tohcello Co., Ltd.). α3: Biaxially oriented polypropylene film (product name: P2111, thickness 20 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α4: Biaxially oriented polypropylene film (product name: P2102, thickness 20 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α5: Biaxially oriented polypropylene film (product name: VPH2011, thickness 20 μm, one side corona treated, average particle size of AB agent on the corona treated side 2 μm, manufactured by AJPlast). α6: Biaxially oriented polypropylene film (product name: PB210J, thickness 20 μm, one-sided corona treatment, manufactured by Futamura Chemical Co., Ltd.). α7: Biaxially oriented polypropylene film (product name: U-1, thickness 20 μm, one-sided corona treatment, manufactured by Mitsui Chemicals Tohcello Co., Ltd.). α8: Biaxially oriented polypropylene film (product name: P2171, thickness 20 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α9: Biaxially oriented polypropylene film (product name: P2161, thickness 20 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α10: Biaxially oriented polypropylene film (product name: VPH2011, thickness 20 μm, one side corona treated, average particle size of AB agent on the corona treated side 4 μm, manufactured by AJPlast).

[0102] <Production Example 1> Acrylic polyol Acrydic CL-1000 (DIC Corporation) was used as the acrylic polyol, and the TDI type hardener Coronate 2030 (Tosoh Corporation) was used as the isocyanate compound, and the acrylic polyol and isocyanate compound were mixed in a solids weight ratio of 6:4, and a mixed liquid (solids content: 2% by mass) for forming the undercoat layer was prepared using a dilution solvent (ethyl acetate).

[0103] <Production Example 2> An aqueous solution of polyvinyl alcohol resin (PVA, product name: Poval PVA-105, manufactured by Kuraray Co., Ltd., polyvinyl alcohol with a degree of saponification of 98-99% and a degree of polymerization of 500) was dissolved, and an aqueous solution of tetraethoxysilane (TEOS) and γ-glycidoxypropyltrimethoxysilane (GPTMS, product name: KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) was prepared by hydrolyzing the aqueous solution with 0.02 mol / L of hydrochloric acid. The aqueous solutions were mixed so that the weight ratio of PVA:TEOS:GPTMS before hydrolysis was 40:50:10. Furthermore, a dilution solvent was added so that the solvent components of the mixed aqueous solution had a mass ratio of water:isopropyl alcohol of 90:10, and a coating agent (5 mass%) for forming an organic-inorganic composite film was prepared.

[0104] [Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-4] The mixed solution for forming the undercoat layer prepared in Production Example 1 was applied to the corona-treated surface of the resin substrate described in Table 1 using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, a vacuum deposition device using an electron beam heating system was used to evaporate a mixed material containing two or more of metal silicon, silicon monoxide, and silicon dioxide, thereby forming an inorganic oxide layer made of silicon oxide having a thickness of 30 nm on the undercoat layer. Next, the coating agent for forming the organic-inorganic composite coating prepared in Production Example 2 was applied to the inorganic oxide layer formed using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming an oxygen barrier coating made of an organic-inorganic composite coating having a thickness of 0.3 μm, thereby obtaining gas barrier films of Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-4.

[0105] The evaluation items and measurement methods in each of the examples and comparative examples are shown below. <Infrared spectroscopic measurement of the first and second surfaces> Using a Fourier transform infrared spectrophotometer FT / IR-4000 (manufactured by JASCO Corporation), measurements were performed on both sides in the thickness direction of each substrate before the gas barrier film was produced. The measurement conditions were as follows. Measurement conditions: ATR method Prism: Ge Resolution: 4cm -1 Accumulation count: 64

[0106] <Number of particles and average protruding height> The surface of the first surface 10a was observed using a laser microscope LEXT OLS-4000 (manufactured by Olympus Corporation), and the number of particles per unit area and the protruding height were measured. The observation magnification was 50 times. The number per unit area was measured in a randomly selected area of ​​257 μm × 259 μm (area 0.067 mm 2 ) and two adjacent areas of the same size to the right of it, and the arithmetic average of the three areas was used. The protrusion height was the arithmetic average of all the fine particles counted in the three areas.

[0107] <Oxygen barrier properties after hot water treatment> The gas barrier film of each example was laminated with a CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort processing having a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac (registered trademark) A620 (base agent) / Takenate (registered trademark) A65 (curing agent), and the CPP was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), which was dry laminated using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40° C. for 3 days. The oxygen barrier coating of the gas barrier film was placed on the adhesive side.

[0108] The resulting gas barrier laminate film was used to prepare an A5-sized pouch with four sides sealed, which was filled with 150 ml of tap water and subjected to heat sterilization treatment (retort treatment) in hot water at 120° C. for 30 minutes.

[0109] The gas barrier laminate film after the hot water treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 ·day·atm) was measured.

[0110] <Adhesion strength after hot water treatment> Immediately after production of the pouches of each example produced by the above procedure and after hot water treatment, test pieces were cut out from the part of the pouch that had been in contact with the contents of each example in accordance with JIS Z1707, and the peel strength of the gas barrier layer 20 was measured as an index of adhesion using an Orientec Co., Ltd. Tensilon universal testing machine RTC-1250. Measurements were performed for two types of peeling, T-type peeling and 180° peeling, both in normal (dry) and with the measurement site wet (wet).

[0111] The measurement results of Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-4 are shown in Table 1.

[0112] [Table 1]

[0113] From the results shown in Table 1, the gas barrier films of Examples 1-1 to 1-6 had a value of formula (1) of 1.65 or less on the first surface, and all of them maintained high adhesion between the substrate 10 and the sealant layer 18 after hot water treatment. In addition, the oxygen permeability was 5.0 cc / m 2 The gas barrier performance was excellent, with a gas barrier strength of less than 1000 m / day atm.

[0114] On the other hand, in the gas barrier films of Comparative Examples 1-1 to 1-3, the value of formula (1) on the first surface was greater than 1.65, and the adhesion after hot water treatment was poor. In the gas barrier film of Comparative Example 1-4, the average protruding height of the fine particles 16 was greater than 2.5 μm, and the oxygen permeability after hot water treatment was 5.0 cc / m 2 ·day·atm and good gas barrier performance was not obtained.

[0115] <Production Example 3> 20 parts by mass of an aqueous solution of polyacrylic acid with a number average molecular weight of 200,000 (Toagosei Aron A-10H, solid content concentration 25% by mass) was diluted with 58.9 parts by mass of distilled water. Then, 0.44 parts by mass of aminopropyltrimethoxysilane (APTMS, Aldrich) was added and stirred to form a uniform solution, preparing a coating agent whose main component is a polycarboxylic acid polymer.

[0116] <Production Example 4> A coating agent containing a polyvalent metal compound as a main component was prepared by mixing 100 parts by mass of an aqueous dispersion of zinc oxide particles (ZE143 manufactured by Sumitomo Osaka Cement) and 2 parts by mass of a hardener Liofol HAERTER UR 5889-21 (manufactured by Henkel).

[0117] [Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-4] On the corona-treated surface of the resin substrate described in Table 2, the mixed solution for forming the undercoat layer prepared in Production Example 1 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, the coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 3 was applied to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.2 μm thick polycarboxylic acid polymer film. Further, the coating agent mainly composed of the polyvalent metal compound prepared in Production Example 4 was applied using a gravure printer on the polycarboxylic acid polymer film to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.2 μm thick polyvalent metal compound film, thereby forming an oxygen barrier film consisting of a polyvalent metal salt film of polycarboxylic acid, and the gas barrier films of Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-4 were obtained.

[0118] [Examples 2-7 to 2-10 and Comparative Examples 2-5 to 2-6] The mixed solution for forming the underlayer prepared in Production Example 1 was applied to the corona-treated surface of the resin substrate shown in Table 2 using a gravure printer to form a coating film, and the coating film was passed through a 100°C oven for 10 seconds to dry, forming an underlayer with a thickness of 0.1 µm. Next, a vacuum deposition apparatus using an electron beam heating system was used to evaporate a mixed material containing two or more of silicon metal, silicon monoxide, and silicon dioxide, to form an inorganic oxide layer made of silicon oxide and having a thickness of 30 nm on the underlayer. Next, a coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 3 was applied onto the inorganic oxide layer using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polycarboxylic acid polymer film with a thickness of 0.2 μm. Further, a coating agent mainly composed of the polyvalent metal compound prepared in Production Example 4 was applied onto the polycarboxylic acid polymer film using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polyvalent metal compound film with a thickness of 0.2 μm. Thus, an oxygen barrier film composed of a polyvalent metal salt of polycarboxylic acid was formed, and the gas barrier films of Examples 2-7 to 2-10 and Comparative Examples 2-5 to 2-6 were obtained.

[0119] [Examples 2-11 to 2-14 and Comparative Examples 2-7 to 2-8] The mixed solution for forming the underlayer prepared in Production Example 1 was applied to the corona-treated surface of the resin substrate shown in Table 2 using a gravure printer to form a coating film, which was then passed through a 100°C oven for 10 seconds to dry, forming an underlayer with a thickness of 0.1 µm. Next, metallic aluminum was evaporated using a vacuum deposition device using an electron beam heating system, and oxygen gas was introduced therein to form an inorganic oxide layer made of aluminum oxide with a thickness of 20 nm on the underlayer. Next, a coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 3 was applied onto the inorganic oxide layer using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polycarboxylic acid polymer film with a thickness of 0.2 μm. Further, a coating agent mainly composed of the polyvalent metal compound prepared in Production Example 4 was applied onto the polycarboxylic acid polymer film using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polyvalent metal compound film with a thickness of 0.2 μm. Thus, an oxygen barrier film composed of a polyvalent metal salt of polycarboxylic acid was formed, and the gas barrier films of Examples 2-11 to 2-14 and Comparative Examples 2-7 to 2-8 were obtained.

[0120] [Table 2]

[0121] From the results shown in Table 2, the gas barrier films of Examples 2-1 to 2-14 had a value of formula (1) of 1.65 or less on the first surface, and all of them maintained high adhesion between the substrate 10 and the sealant layer 18 after hot water treatment. In addition, the oxygen permeability was 5.0 cc / m 2 The gas barrier performance was excellent, with a gas barrier strength of less than 1000 m / day atm.

[0122] On the other hand, the gas barrier films of Comparative Examples 2-1 to 2-3 and 2-5 to 2-8 had a value of formula (1) of more than 1.65 on the first surface, and had low adhesion after hot water treatment. The gas barrier film of Comparative Example 2-4 had an average protruding height of the fine particles 16 of more than 2.5 μm and an oxygen permeability of 5.0 cc / m 2 ·day·atm and good gas barrier performance was not obtained.

[0123] The above describes one embodiment of the present invention and examples. However, the specific configuration is not limited to this embodiment, and configuration changes and combinations that do not deviate from the gist of the present invention are also included.

[0124] In addition, the gas barrier film of the present invention may have a printed layer at an appropriate position. Also, an intervening film may be attached onto the covering layer to impart desired physical properties such as pinhole resistance, cold resistance, heat resistance, bag drop resistance, and tear resistance to the gas barrier film.

[0125] Furthermore, in the gas barrier film of the present invention, an adhesive layer or a sealant layer is not essential, that is, the adhesive layer or the sealant layer may be provided as necessary, taking into consideration the specific use of the gas barrier film, etc. [Industrial Applicability]

[0126] The gas barrier film of the present invention exhibits excellent adhesion strength and gas barrier properties even after hot water treatment. In addition, the quality can be stabilized even if the oxygen barrier coating is made thin, and raw material costs can be reduced.

[0127] The gas barrier film of the present invention can be suitably used, for example, as a packaging material, and can also be suitably used as a packaging material for boiling treatment and retort treatment. By using the gas barrier film of the present invention as a packaging material, the quality retention of the contents can be improved.

[0128] The gas barrier film of the present invention can be used for purposes other than packaging materials, such as electronic device-related films, solar cell films, various functional films for fuel cells, and substrate films. [Explanation of symbols]

[0129] 100 Gas barrier film 10 Resin substrate 11 Resin base material surface layer 12 Resin base material base layer 13 Base layer 14 Inorganic oxide layer 15 Oxygen barrier coating 16 Fine particles 17 Adhesive layer 18 Sealant Layer

Claims

1. A base material mainly composed of polypropylene; The substrate has an oxygen barrier coating (excluding those containing an inorganic layered compound) on a first surface side thereof, a base layer, or both a base layer and an inorganic oxide layer, between the substrate and the oxygen barrier coating; In infrared spectroscopy of the first surface, 1360 to 1390 cm -1 The peak intensity I1 present at 1440 to 1480 cm -1 The ratio of the peak intensity I2 present in satisfies the following formula (1), I1 / I2≦1.55…(1) the first surface has protruding particles formed of a material other than polypropylene; The number of the fine particles is 257 μm × 259 μm (area 0.067 mm 2 ) or less than 100 pieces per A gas barrier film, wherein the fine particles have an average protrusion height of 2.5 μm or less.

2. The substrate is The substrate has two or more resin layers including a base layer and a surface layer constituting the first surface, The I1 / I2 value in infrared spectroscopy of the resin layer on the second surface opposite to the first surface is The gas barrier film according to claim 1 , wherein the I1 / I2 value is greater than the I1 / I2 value on the first surface.

3. 3. The gas barrier film according to claim 1, wherein the undercoat layer has a thickness of 0.01 to 1 μm.

4. The underlayer contains an organic polymer as a main component, The gas barrier film according to any one of claims 1 to 3, wherein the organic polymer comprises at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, or a reaction product of these organic polymers.

5. the underlayer and the inorganic oxide layer are provided between the substrate and the oxygen barrier coating, The gas barrier film according to any one of claims 1 to 4, wherein the inorganic oxide layer has a thickness of 1 to 200 nm.

6. the underlayer and the inorganic oxide layer are provided between the substrate and the oxygen barrier coating, The gas barrier film according to any one of claims 1 to 5, wherein the inorganic oxide layer is aluminum oxide or silicon oxide.

7. The gas barrier film according to any one of claims 1 to 6, wherein the oxygen barrier coating has a thickness of 0.05 to 1 µm.

8. 8. The gas barrier film according to claim 1, wherein the oxygen barrier coating is a coating containing at least one of a metal alkoxide, a hydrolysate thereof, and a reaction product thereof, and a water-soluble polymer.

9. 9. The gas barrier film according to claim 8, wherein the oxygen barrier coating further comprises at least one of a silane coupling agent, a hydrolyzate thereof, and a reaction product thereof.

10. The gas barrier film according to any one of claims 1 to 7, wherein the oxygen barrier coating contains a polyvalent metal salt of a carboxylic acid which is a reaction product between a carboxy group of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B).

11. The gas barrier film according to any one of claims 1 to 10, wherein the substrate further comprises a heat-sealable sealant layer, the sealant layer being bonded to the oxygen barrier coating by an adhesive layer.

12. After hot water treatment at 120°C for 30 minutes, Oxygen permeability is 5.0cc / m 2 ・day or less, The gas barrier film according to claim 11, wherein the peel strength between the substrate and the sealant layer is 1.0 N / 15 mm or more.

Citation Information

Patent Citations

  • Transparent laminated body

    JP1998264292A

  • Plastic film laminate

    JP2000043219A

  • Plastic base material and gas-barrier film using it

    JP2002113826A

  • Laminate film

    JP2006062258A

  • Packaging material and its manufacturing method

    JP2008200990A